2018
DOI: 10.1016/j.celrep.2018.05.071
|View full text |Cite
|
Sign up to set email alerts
|

Hif1α Deletion Limits Tissue Regeneration via Aberrant B Cell Accumulation in Experimental Pancreatitis

Abstract: SUMMARY Pancreatitis is an inflammatory disease of the exocrine pancreas and ranks among the most common gastrointestinal disorders. Inflamed tissues frequently experience conditions of insufficient oxygen availability, or hypoxia. Here we demonstrate that hypoxia and consequent stabilization of the hypoxia-inducible factor 1α (HIF1α) transcription factor occur in murine and human pancreatitis. Mice lacking pancreas-specific HIF1α expression displayed markedly impaired pancreatic regeneration following cerulei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“… 59 A recent study with an experimental CP model suggests a pathogenic role for B cells in tissue regeneration. 60 Our scRNA-seq analysis revealed significantly increased frequencies of B cells and plasma cells in both CP groups, with differential gene expression signatures between hereditary and idiopathic CP ( online supplemental figure 12A, B ). These data implicate B cells, along with other immune subsets, in the immunopathogenic mechanisms of CP and requires future investigation.…”
Section: Discussionmentioning
confidence: 82%
“… 59 A recent study with an experimental CP model suggests a pathogenic role for B cells in tissue regeneration. 60 Our scRNA-seq analysis revealed significantly increased frequencies of B cells and plasma cells in both CP groups, with differential gene expression signatures between hereditary and idiopathic CP ( online supplemental figure 12A, B ). These data implicate B cells, along with other immune subsets, in the immunopathogenic mechanisms of CP and requires future investigation.…”
Section: Discussionmentioning
confidence: 82%
“…AMPK, a sensor of intracellular energy, can be activated at low energy levels and regulate cellular processes . SAP, an inflammatory disease of the exocrine pancreas, induces tissue hypoxia . GSEA indicated that HALLMARK_HYPOXIA was significantly up-regulated in SAP (SI Table S8).…”
Section: Discussionmentioning
confidence: 99%
“…38 SAP, an inflammatory disease of the exocrine pancreas, induces tissue hypoxia. 39 GSEA indicated that HALLMARK_HYPOXIA was significantly up-regulated in SAP (SI Table S8). Hypoxia induces oxidative stress, which is an important signal in cellular injury and plays a crucial role in the pathogenesis of SAP.…”
Section: ■ Discussionmentioning
confidence: 99%
“…276 Depletion of B cells increases exocrine tissue regeneration owing to a significant decrease in overall immune infiltrations and fibrosis. 277 Pancreatitis-induced tissue hypoxia and HIF-1α accumulation-induced B-cell depletion enhances pancreatic regeneration. B cell depletion in mice with pancreatitis significantly enhanced tissue regeneration and chemotherapeutic drug resistance.…”
Section: Hypoxia and Angiogenesismentioning
confidence: 99%